NAVIGATING CRISIS: A COMPARATIVE ANALYSIS OF GOLD JEWELRY ARTISANS’ STRATEGIES IN PESAYANGAN VILLAGE, TEGAL REGENCY, DURING THE 1998 AND 2020 CRISES: Bertahan di Tengah krisis: komparasi strategi perajin perhiasan emas di Desa Pesayangan Kabupaten Tegal pada 1998 dan 2020 - nuriyah, sinta; Carolina Santi Muji Utam (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The research aims to analyze how these crises transformed the traditional gold jewelry industry and affected craftsmen's livelihoods, social structures, and cultural practices. Using qualitative methodology with history approaches, data was collected through in-depth interviews, participant observation, and document analysis. The findings reveal that both crises forced craftsmen to diversify their occupations, becoming gold brokers, traders, farmers, and laborers. The economic pressures weakened traditional solidarity systems, transformed gender roles with women taking more active economic roles, and reduced younger generation interest in continuing the craft tradition. The study contributes new insights into crisis resilience strategies in traditional industries and demonstrates how economic shocks create lasting social transformations. The research highlights the vulnerability of traditional crafts to external economic pressures and the adaptive mechanisms communities develop to survive.